Assessing and Improving Hospital Mass-Casualty Preparedness: A No-Notice Exercise. Issue 6 (7th August 2017) - Waxman, Daniel A.; Chan, Edward W.; Pillemer, Francesca; Smith, Timothy WJ; Abir, Mahshid; Nelson, Christopher
Abstract: In recent years, mass-casualty incidents (MCIs) have become more frequent and deadly, while emergency department (ED) crowding has grown steadily worse and widespread. The ability of hospitals to implement an effective mass-casualty surge plan, immediately and expertly, has therefore never been more important. Yet, mass-casualty exercises tend to be highly choreographed, pre-scheduled events that provide limited insight into hospitals' true capacity to respond to a no-notice event under real-world conditions. To address this gap, the US Department of Health and Human Services (Washington, DC USA), Office of the Assistant Secretary for Preparedness and Response (ASPR), sponsored development of a set of tools meant to allow any hospital to run a real-time, no-notice exercise, focusing on the first hour and 15 minutes of a hospital's response to a sudden MCI, with the goals of minimizing burden, maximizing realism, and providing meaningful, outcome-oriented metrics to facilitate self-assessment. The resulting exercise, which was iteratively developed, piloted at nine hospitals nationwide, and completed in 2015, is now freely available for anyone to use or adapt. This report demonstrates the feasibility of implementing a no-notice exercise in the hospital setting and describes insights gained during the development process that might be helpful to future exercise developers. It also introduces the use of ED "immediate bed availability (IBA)" as an objective, dynamic measure of an ED's physical capacity for new arrivals. DA Waxman, EW Chan, F Pillemer, TWJ Smith, M Abir, C Nelson .Assessing and improving hospital mass-casualty preparedness: a no-notice exercise .Prehosp Disaster Med .2017 ;32 (6 ):662 –666 .